Relationship Five Behavioral Indicators and Healthy Living with Tuberculosis Multidrug-Resistant - Mulyanto, Heri (Faculty of Public Health, 2014)
ABSTRACTClean and healthy life style is a behavior that is closely related to the emergence of infectious diseases, including TB continued into MDR-TB. This study aimed to determine the relationship between the 5 behavioral indicators of clean and healthy living with MDR-TB in Dr. Saiful Anwar Hospital. Research was conducted used a retrospective analytic designed by case control study. Subjects drawn from a population with a simple random sampling with a ratio of 1: 1 between cases and controls, patients of MDR-TB in TB clinic as many as 27 patients as cases group and patients who had undergone TB treatment for at least 6 months with a negative smear results by 27 patients as a control group. The variables in this study were healthy and hygienic behavior, and several other variable and MDR-TB The variables in this study were healthy and hygienic behavior, demographic variables and MDR-TB. Research results calculated used Chi Square test with a confidence level of 95% (Î± = 0.05) showed age, gender, education level and marital status was not associated with MDR- TB, nutritional eating life style associated with MDR-TB (OR = 0,25 and p = 0.014), exercise life style (physical activity) associated with MDR-TB (OR = 0,16 and p = 0.00), utilizing life style health care facilities associated with MDR-TB (OR= 0,091 and p = 0.01), life style to prevent co-infections was not associated with MDR-TB (p = 0.78), and the provision of a healthy home environment behaviors associated with TB multidrug-resistant (OR = 0,28 and p = 0.03). There are four variables of clean and healthy life style associated with MDR-TB, so that health care facilities are advised to give the promotion of clean and healthy life style TB patients to prevent progression to MDR-TB.Keywords: Clean and Healthy Life Style, multidrug resistant tuberculosis